Changes in growth and photosynthetic patterns of oil palm (Elaeis guineensis Jacq.) seedlings exposed to short-term CO2 enrichment in a closed top chamber - Ibrahim, Mohd Hafiz; Jaafar, Hawa Z. E.; Harun, Mohd Haniff; Yusop, Mohd Rafii (Springer Verlag, 2010)
Three varieties of oil palm seedlings (Deli Yangambi, Deli Urt, Deli AVROS) were exposed to three levels of CO2 (400, 800, 1,200 μmol/mol) in split plot design to determine growth (net assimilation rate, NAR; relative growth rate, RGR) and photosynthetic patterns of the seedlings under short-term CO2 exposure of 15 weeks. Increasing CO2 from 400 to 800 and 1,200 μmol/mol significantly enhanced total biomass and leaf area, net photosynthesis (A) and water use efficiency (WUE) especially from weeks 9 to 15. By the end of week 15, total biomass increased by 113%, and A and WUE by one- and fivefold, respectively, while specific leaf area decreased by 37%. Both enhanced biomass and A under elevated CO2 were effective in modifying NAR and RGR as shown by high correlation coefficient values (r 2 = 0.68 and 0.72; r 2 = 0.63 and 0.67, respectively), although WUE seemed to have more influence over the NAR (r 2 = 0.97) and RGR (r 2 = 0.93). Neither interspecific preference nor its interaction with CO2 imposed any significant effect on parameters observed. Growth improvement with CO2 seemed able to produce healthy, bigger and vigorous oil palm seedlings, and the technique may have potential to be developed for use to reduce nursery period.